Dependence on video games and social skills in school adolescents - Mendoza Saico, Bertha (2023)
Addictive dependence on video games has become a problem in the youth population that has increased during social confinement, especially in the adolescent population, harming mental health. The objective of the research was to determine the relationship between dependence on video games and social skills in school adolescents. It was based on a quantitative descriptive correlational manner and a population of 97 students from a public school was applied to whom a questionnaire validated by expertise was applied. The results showed a positive relationship between the proposed variables with their respective dimensions, and with a particularly high correlation between dependence on video games and advanced social skills. This concludes by determining that high dependence on video games leads to a low level of development of social skills in a group of adolescents from a public school.